The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1111/petr.13968
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoxemia on pediatric liver transplantation for hepatopulmonary syndrome

Abstract: Background: The treatment of choice for patients with cirrhosis and HPS is LT. The clinical manifestations associated with hypoxemia result in limitations and a poor health-related quality of life of affected patients. The present report aims to study the differences in outcomes between patients with PaO 2 < 50 mm Hg and those with PaO 2 ≥ 50 mm Hg. Methods: This was a retrospective study of 21 patients under 18 years of age conducted from 2001 to 2018; the patients were divided into 2 groups: G1-PaO 2 ≥ 50 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[37] Although there are robust data to support an association between room air oxygenation and posttransplantation survival in adult HPS patients, the largest studies on this topic in children were just recently published and derived from retrospective cohorts of less than 25 patients each. [38,39] The authors observed that although children with very severe HPS (PaO 2 < 50 mm Hg) required longer durations of mechanical ventilation, longer intensive care unit (ICU) and hospital stays, and longer O 2 weaning time than those with mild, moderate, or severe HPS (PaO 2 > 50 mm Hg), there was no difference in mortality across subgroups. Although our findings also indicate that severity of HPS does not impact post-LT survival in children, our analysis expands on the size and depth of this work.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Although there are robust data to support an association between room air oxygenation and posttransplantation survival in adult HPS patients, the largest studies on this topic in children were just recently published and derived from retrospective cohorts of less than 25 patients each. [38,39] The authors observed that although children with very severe HPS (PaO 2 < 50 mm Hg) required longer durations of mechanical ventilation, longer intensive care unit (ICU) and hospital stays, and longer O 2 weaning time than those with mild, moderate, or severe HPS (PaO 2 > 50 mm Hg), there was no difference in mortality across subgroups. Although our findings also indicate that severity of HPS does not impact post-LT survival in children, our analysis expands on the size and depth of this work.…”
Section: Discussionmentioning
confidence: 99%
“…94,[105][106][107][108] In single-center studies, children with very severe HPS (PaO 2 < 50 mm Hg) had longer need for supplementation oxygen, mechanical ventilator, and ICU stay as compared with children with less severe degrees of hypoxemia. 93,109 Additional management strategies in children with HPS and persistent hypoxemia have been reported including the use of inhaled NO and high-flow nasal cannula and even in these children, eventual resolution of HPS is achieved. 110,111…”
Section: Management Of Hpsmentioning
confidence: 99%